The Influence of Organizational Culture on Employee Job Satisfaction and Performance in the Public Sector - Imha, Ulia Arbarehan; Rao, Don Gusti; Rahimi, Ramin (World Psychology, 2025)
Organizational culture plays a pivotal role in shaping employee job satisfaction and performance, particularly in the public sector where the nature of work is often influenced by public service values and government policies. A positive organizational culture is associated with increased motivation, job satisfaction, and improved performance, whereas a negative culture can lead to disengagement and inefficiency. Despite its importance, there is limited research on how organizational culture specifically impacts employee job satisfaction and performance in the public sector, especially in non-Western contexts. This study aims to explore the relationship between organizational culture, job satisfaction, and employee performance in public sector organizations. A quantitative research design was employed, using surveys distributed to 300 employees from various public institutions. Data were analyzed using regression analysis to examine how dimensions of organizational culture, such as values, communication, and leadership styles, influence job satisfaction and performance. The results indicate that organizational culture has a significant positive impact on both job satisfaction and performance. Employees who perceived their work environment as supportive, inclusive, and aligned with organizational values reported higher levels of satisfaction and better performance. The study concludes that fostering a positive organizational culture is essential for enhancing employee outcomes in the public sector, and recommends targeted interventions to cultivate such a culture.